The Influence of Corporate Social Responsibility on Firm Value With Institutional Ownership and Managerial Ownership as Moderating Variables - Rosa Salsa Bila; Suherman; Agung Dharmawan Buchdadi (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2022)
This study aims to determine the effect of Corporate Social Responsibility (CSR) on firm value, with institutional ownership and managerial ownership as moderating variables in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2019 period. The data used for the research sample is in the form of annual reports from manufacturing companies listed on the IDX for the 2014-2019 period. The method used for the sampling process is the purposive sampling technique, while the model used in this study is panel data with a random-effects model approach. The results of this study indicate that CSR does not have a significant effect on firm value. Institutional ownership as a moderating variable cannot moderate the relationship between CSR and firm value. Meanwhile, managerial ownership is shown to moderate the relationship between CSR and firm value but has a weakening effect.